Built to Bite: Feeding Kinematics, Bite Forces, and Head Shape of a Specialized Durophagous Lizard, Dracaena Guianensis (Teiidae) - Schaerlaeken, Vicky; Holanova, Veronika; Boistel, R.; Aerts, Peter; Velensky, Petr; Rehak, Ivan; Andrade, Denis V.; Herrel, Anthony (Wiley-Blackwell, 2012)
Most lizards feed on a variety of food items that may differ dramatically in their physical and behavioral characteristics. Several lizard families are known to feed upon hard-shelled prey (durophagy). Yet, specializations toward true molluscivory have been documented for only a few species. As snails are hard and brittle food items, it has been suggested that a specialized cranial morphology, high bite forces, and an adapted feeding strategy are important for such lizards. Here we compare head and skull morphology, bite forces, and feeding kinematics of a snail-crushing teiid lizard (Dracaena guianensis) with those in a closely related omnivorous species (Tupinambis merianae). Our data show that juvenile D. guianensis differ from T. merianae in having bigger heads and greater bite forces. Adults, however, do not differ in bite force. A comparison of feeding kinematics in adult Dracaena and Tupinambis revealed that Dracaena typically use more transport cycles, yet are more agile in manipulating snails. During transport, the tongue plays an important role in manipulating and expelling shell fragments before swallowing. Although Dracaena is slow, these animals are very effective in crushing and processing hard-shelled prey. J. Exp. Zool. 317A:371381, 2012. (c) 2012 Wiley Periodicals, Inc.